Antidepressant Discontinuation Syndrome –A Case Report - Navin Kumar Devaraj; Aneesa Abdul Rashid; Khadijah Hasanah Abang Abdullah; Abdul Hadi Abdul Manap (Faculty of Medicine and Surgery, University of Malta, 2024)
Volume :33 Issue: 1 (page: 116-120)